2014
DOI: 10.1200/jco.2014.55.7348
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Pazopanib in Maintenance Therapy of Ovarian Cancer

Abstract: Pazopanib maintenance therapy provided a median improvement of 5.6 months (HR, 0.77) in progression-free survival in patients with advanced ovarian cancer who have not progressed after first-line chemotherapy. Overall survival data to this point did not suggest any benefit. Additional analysis should help to identify subgroups of patients in whom improved efficacy may balance toxicity (NCT00866697).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
217
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 302 publications
(226 citation statements)
references
References 25 publications
5
217
0
4
Order By: Relevance
“…However, it has proven exceptionally difficult to show a statistically significant prolongation of OS with the addition of targeted therapy to standard treatments in patients with ovarian cancer [10][11][12][13][14][15][16][17][18][26][27][28]. Potential confounding factors for OS include the long postprogression survival period, the administration of multiple postprogression therapies, and the potential for postprogression crossover [27,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has proven exceptionally difficult to show a statistically significant prolongation of OS with the addition of targeted therapy to standard treatments in patients with ovarian cancer [10][11][12][13][14][15][16][17][18][26][27][28]. Potential confounding factors for OS include the long postprogression survival period, the administration of multiple postprogression therapies, and the potential for postprogression crossover [27,29].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that the Ang2 pathway plays a role in the pathophysiology of ovarian cancer [6][7][8] and upregulation of Ang2 is correlated with poor prognosis in women with recurrent ovarian cancer [9]. Several antiangiogenic agents that target the VEGF pathway have been shown to improve progression-free survival (PFS) in patients with ovarian cancer; however, a statistically significant improvement in OS has not been demonstrated [10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Pazopanib has also been studied for use in maintenance therapy, resulting in an increase in PFS, but no improvement in overall survival (156). Pazopanib is also associated with a significant toxicity profile such as fatigue, gastrointestinal toxicities (such as nausea and/or diarrhoea), hypertension and myelosuppression (156).…”
Section: [H1]managementmentioning
confidence: 99%
“…Pazopanib is also associated with a significant toxicity profile such as fatigue, gastrointestinal toxicities (such as nausea and/or diarrhoea), hypertension and myelosuppression (156).…”
Section: [H1]managementmentioning
confidence: 99%
“…The GOG218 and ICON7 studies showed that progression-free survival (PFS) was significantly extended, but there were no significant differences in overall survival (OS). 19,20 Other drugs that have been clinically applied are the multi-targeted tyrosine kinase inhibitor pazopanib, 21 the mammalian target of rapamycin (mTOR) inhibitor temsirolimus, 22 and the angiopoietin inhibitor trebananib. 23 Although these molecularly targeted drugs are effective at extending PFS, no studies have indicated that they significantly extend OS.…”
Section: Ismail Et Al Reported That Mouse Cancer Cells In Which Cbr1mentioning
confidence: 99%